Pelatihan Da’i dalam Program Dakwah Qurawiyah Sebagai Upaya Penguatan Akidah di Pondok Pesantren Al-Ishlah Bondowoso - Raadliyatush Shalihah; Muhammad Habibi Hamzah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service activity aims to improve the competence of da’i in the Qurawiyah Da’wah Program as an effort to strengthen aqidah at Pondok Pesantren Al-Ishlah Bondowoso. This activity is part of the Qurawiyah Da’wah Program, which is regularly organized and was conducted in February 2026 prior to the deployment of da’i to selected areas. The implementation method consisted of several stages: (1) presentation of materials related to da’wah and aqidah strengthening, (2) assignment for participants to develop aqidah-based da’wah materials, (3) demonstration by selected participants presenting their work in front of trainers and peers, and (4) evaluation through question-and-answer sessions and feedback on participants’ assignments.The results indicate that the training improved participants’ understanding of aqidah as well as their skills in developing and delivering structured and communicative da’wah materials. Therefore, this da’i training within the Qurawiyah Da’wah Program serves as an effective strategy to support the strengthening of community aqidah through enhancing the quality of da’i human resources